From the enemy-centric to people-centric approach: Views and attitudes of Mozambicans living in Johannesburg towards SAMIM’s counterinsurgency in Cabo Delgado - Makanda, Joseph (Sabinet, 2024)
The Southern African Mission in Mozambique (SAMIM) has been relatively under-researched in view of its conception among Mozambicans. This study used views, insights and attitudes of Mozambicans in Johannesburg, South Africa on the relevance of the SAMIM‟s counterinsurgency efforts in Cabo Delgado. While the deployment of the SAMIM‟s forces serve to minimise the effects of terrorism and set a platform on which addressing the root causes of insurgency and is motivated by the desire for lasting peace, the findings of this study revealed that it falls short of addressing high levels of poverty, marginalises the views of disgruntled Mozambicans, and cannot address regional disparities between the southerners and northerners in Mozambique. Consequently, the participants argued that the SAMIM‟s approach holds no prospect of denying insurgency the necessary sustenance and support to survive. The study recommended leveraging the use of local assemblies and incorporating views of marginalised and disgruntled Mozambicans within the SAMIM‟s counterinsurgency strategy to address structural violence that abets and sustains insurgents in Cabo Delgado.